The Development and Validation of Financial Management Behavior (FMB) Scale in Postgraduate Students - Andi Amri; Zulmi Ramdani; Jaka Warsihna; Lidwina Felisima Tae (Jurnal Manajemen Indonesia, 2022)
This study aims to develop and validate a financial management behavior scale. This study used the approach of measuring instrument modification by applying the existing theory into a statement that will be used as an instrument to see the condition of a person's financial management behavior. The researchers used the basic theory of Dew and Xiao (2011) which divides financial management behavior into the consumption dimension, cash flow management dimension, savings and investment dimension, and debt management dimension. The subjects involved in this study were 391 people who were postgraduate students in the capital city of Jakarta and were selected using a purposive sampling technique. Structural equation modeling (SEM) analysis with AMOS software were used in this study. The results of the analysis showed that the financial management behavior scale developed by the researchers has met the fit model and produced a valid statement which is ready to be used to measure the behavioral conditions of one's financial management specifically in the student context. The limitations and suggestions will be discussed further in this article. Keywords— Financial Management; Financial Management Behaviour; Scale Development; Scale Validation